2015
DOI: 10.1111/mmi.12943
|View full text |Cite
|
Sign up to set email alerts
|

Rot is a key regulator of Staphylococcus aureus biofilm formation

Abstract: AUTHOR SUMMARY Staphylococcus aureus is a significant cause of chronic biofilm infections on medical implants. We investigated the biofilm regulatory cascade and discovered that the repressor of toxins (Rot) is part of this pathway. A USA300 community-associated methicillin-resistant S. aureus (CA-MRSA) strain deficient in Rot was unable to form a biofilm using multiple different assays, and we found rot mutants in other strain lineages were also biofilm deficient. By performing a global analysis of transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 64 publications
9
63
0
Order By: Relevance
“…Additionally, a gene ontology analysis using GoMiner (43) identified genes in the category of pathogenesis, including proteases (spl, ssp, and aur) and toxins, as the most highly enriched category of genes that are overexpressed in the ⌬sarA mutant, consistent with previous ⌬sarA mutant transcriptomics studies (60)(61)(62)(63). Interestingly, the ⌬sarA mutant is not the only NO˙-sensitive mutant we identified that overproduces proteases; the ⌬codY and ⌬rot mutants have also been characterized as overproducers of at least several of the 10 extracellular proteases secreted by S. aureus (64)(65)(66)(67)(68)(69). SarA and Rot directly repress protease transcription, whereas CodY indirectly represses protease transcription by repressing agrA (Fig.…”
Section: Resultssupporting
confidence: 71%
“…Additionally, a gene ontology analysis using GoMiner (43) identified genes in the category of pathogenesis, including proteases (spl, ssp, and aur) and toxins, as the most highly enriched category of genes that are overexpressed in the ⌬sarA mutant, consistent with previous ⌬sarA mutant transcriptomics studies (60)(61)(62)(63). Interestingly, the ⌬sarA mutant is not the only NO˙-sensitive mutant we identified that overproduces proteases; the ⌬codY and ⌬rot mutants have also been characterized as overproducers of at least several of the 10 extracellular proteases secreted by S. aureus (64)(65)(66)(67)(68)(69). SarA and Rot directly repress protease transcription, whereas CodY indirectly represses protease transcription by repressing agrA (Fig.…”
Section: Resultssupporting
confidence: 71%
“…S. aureus biofilm studies to date have mostly been performed using commercially available rich or chemically defined media, which has provided a wealth of information about important bacterial contributors to the biofilm process, but these defined growth conditions have limited application to the host environment. In some studies, human matrix proteins have been used to aid S. aureus attachment and enhance biofilm accumulation (35)(36)(37)(38), providing a biotic substratum that better imitates a realistic host surface. Although these approaches are an improvement and likely enhance the relevance of biofilm observations, the abundance of host glycosaminoglycans in many tissues and their contribution to S. aureus biofilm formation remain mostly overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this allelic organization in the chromosome, the expression of cap5 and cap8 genes is subject to similar transcriptional regulation. To date, a large number of regulators affecting cap gene transcription, some of which are non-DNA-binding factors, have been identified and/or characterized, and they include MgrA, AgrADBC, ArlRS, SaeRS, CodY, KdpDE, SigB, SpoVG, ClpC, ClpP, SbcDC, RpiRC, CcpA, Rot, CcpE, and AirSR (4)(5)(6)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Because of this allelic organization in the chromosome, the expression of cap5 and cap8 genes is subject to similar transcriptional regulation. To date, a large number of regulators affecting cap gene transcription, some of which are non-DNA-binding factors, have been identified and/or characterized, and they include MgrA, AgrADBC, ArlRS, SaeRS, CodY, KdpDE, SigB, SpoVG, ClpC, ClpP, SbcDC, RpiRC, CcpA, Rot, CcpE,[12][13][14][15][16][17][18][19][20].Staphylococcal capsules are involved in immune evasion, but they can also mask cell surface components, such as adhesins, that are important for pathogenesis (21,22). Thus, the production of capsule must be controlled properly depending on the conditions of the environment in which S. aureus resides.…”
mentioning
confidence: 99%